Science and Qur'an Integrated Curriculum Model in Preparing Competencies for Religious Critical Graduates - Triana Dewi; Anib Dwi Saputro; Azid Syukroni; Syamsul Arifin (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
Islamic basic education faces ongoing challenges in integrating scientific mastery with the internalization of religious values, particularly in pioneering madrasas. This study aims to describe the integrated curriculum model of science and the Qur’an and analyze its implementation in developing critical and religious competencies at Madrasah Ibtidaiyah Modern Sainqu Ponorogo. Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving the head of the madrasah and teachers. Data were analyzed using descriptive qualitative techniques, including data reduction, presentation, and conclusion drawing. The findings indicate that MIM Sainqu Ponorogo implements the integrated curriculum flexibly and gradually, in accordance with elementary students’ developmental characteristics. The integration of science and the Qur’an is carried out through thematic learning and experiential activities, such as outing classes that connect natural phenomena with monotheistic values. Daily religious practices, including Dhuha prayers and Qur’anic memorization, strengthen character formation. Despite limitations in facilities and human resources, adaptive and collaborative strategies enable effective implementation. The study concludes that this integrated curriculum effectively supports the development of critical, religious, and well-rounded graduates.